2018
DOI: 10.1002/ijc.31978
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of mtSSB by interleukin‐6 promotes cell growth through mitochondrial biogenesis‐mediated telomerase activation in colorectal cancer

Abstract: It is now widely accepted that mitochondrial biogenesis is inhibited in most cancer cells. Interestingly, one of the possible exceptions is colorectal cancer (CRC), in which the content of mitochondria has been found to be higher than in normal colon mucosa. However, to date, the causes and effects of this phenomenon are still unclear. In the present study, we systematically investigated the functional role of mitochondrial single‐strand DNA binding protein (mtSSB), a key molecule in the regulation of mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…We found that this is due to a compensatory response initiated by a transcriptional activation of the mitochondrial stress response master regulator CEBPβ, which acts to increase mitochondrial biogenesis in concert with ATF4 and CHOP via TFAM but also by increasing cellular proliferation in the liver via increased telomerase expression (Fig ). This is a previously unreported transcriptional response that appears to be distinct from the post‐transcriptional signaling pathways that increase mitochondrial biogenesis in response to energy demands (Morita et al , ) or that upregulate telomerase in response to increased mitochondrial biogenesis (Wang et al , ), as both of these act via the mTOR pathway, that is not activated by the low levels of stress that result from mitochondrial mistranslation in our model. Post‐transcriptional responses are more rapid than transcriptional responses and are better suited to deal with extreme stresses, while the transcriptional responses we observe are potentially better suited to improve the stability of mitochondrial function over a longer timeline.…”
Section: Discussionmentioning
confidence: 61%
“…We found that this is due to a compensatory response initiated by a transcriptional activation of the mitochondrial stress response master regulator CEBPβ, which acts to increase mitochondrial biogenesis in concert with ATF4 and CHOP via TFAM but also by increasing cellular proliferation in the liver via increased telomerase expression (Fig ). This is a previously unreported transcriptional response that appears to be distinct from the post‐transcriptional signaling pathways that increase mitochondrial biogenesis in response to energy demands (Morita et al , ) or that upregulate telomerase in response to increased mitochondrial biogenesis (Wang et al , ), as both of these act via the mTOR pathway, that is not activated by the low levels of stress that result from mitochondrial mistranslation in our model. Post‐transcriptional responses are more rapid than transcriptional responses and are better suited to deal with extreme stresses, while the transcriptional responses we observe are potentially better suited to improve the stability of mitochondrial function over a longer timeline.…”
Section: Discussionmentioning
confidence: 61%
“…The expressed mtSSB activates the ROS/Akt/mTOR pathway, which up-regulates telomerase reverse transcriptase (TERT), which stabilizes telomeres and thereby helps immortalize CRC cells. 54…”
Section: Cell Cycle Progressionmentioning
confidence: 99%
“…Remarkably, FOXP1 is identified to act as an oncogene, and its overexpression confers a poor prognosis in various types of cancers [43][44][45][46]. A recent study has demonstrated that FOXP1 participated in promoting the proliferation of CRC cells, and its high expression suggests poor prognosis of CRC patients [47].…”
Section: Discussionmentioning
confidence: 99%